New micromechanical data and modelling framework for the elastic response of calcareous mudstones. (October 2022) - Graham, S.P.; Rouainia, M.; Aplin, A.C.; Ireland, M.T.; Charlton, T.S.; Armitage, P.J.
Abstract: Mudstones are amongst the most compositionally diverse sedimentary materials in nature; constraining their elastic properties is crucial in many subsurface engineering scenarios. Mudstones with high calcium carbonate contents are common but have received little attention in micromechanical studies. Using the Eagle Ford formation as an example, we present a new conceptual framework for micromechanical modelling calcareous mudstones, with the aim of predicting the macroscopic elastic response of mudstones to address gaps left by limited core-scale data. The model accounts for the microstructural differences with argillaceous mudstones and implement it in a mean-field homogenisation framework. This allows us to model elastic stiffness from the scale of microcrystalline calcite up to the scale of the undamaged poro-mineralogical skeleton. We present results of a comprehensive micromechanical characterisation of the Eagle Ford, adding to the data available for calcareous mudstones. We show that the contribution of calcite to the overall anisotropy is non-negligible, with appropriate transversely isotropic elastic constants for the carbonate phase calculated. We demonstrate the use of high-load nanoindentation tests to successfully calibrate a micromechanical model. This is achieved by direct comparison of model results against the inversion of high-load indentation data. Finally, the applicability of our modelling scheme and material parameters to model other calcareous mudstones is explored using core-scale data from the Williston basin of Canada, demonstrating good agreement.